2008
DOI: 10.1261/rna.1052008
|View full text |Cite
|
Sign up to set email alerts
|

Conifers have a unique small RNA silencing signature

Abstract: Plants produce small RNAs to negatively regulate genes, viral nucleic acids, and repetitive elements at either the transcriptional or post-transcriptional level in a process that is referred to as RNA silencing. While RNA silencing has been extensively studied across the different phyla of the animal kingdom (e.g., mouse, fly, worm), similar studies in the plant kingdom have focused primarily on angiosperms, thus limiting evolutionary studies of RNA silencing in plants. Here we report on an unexpected phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 39 publications
6
86
0
Order By: Relevance
“…5B). The major peak was at 24 nt in wild-type N. benthamiana plants, as it is usual in angiosperm plant species (Dolgosheina et al 2008), but shifted to 21 nt upon P1b expression. Although this enrichment in 21-nt small RNAs is probably the result of specific P1b binding and consequent stabilization, additional experiments are necessary to rule out possible effects of P1b in enhancing 21-nt small RNA synthesis or 24-nt small RNA degradation, or in repression of the accumulation of the 24-nt species.…”
Section: Discussionmentioning
confidence: 57%
“…5B). The major peak was at 24 nt in wild-type N. benthamiana plants, as it is usual in angiosperm plant species (Dolgosheina et al 2008), but shifted to 21 nt upon P1b expression. Although this enrichment in 21-nt small RNAs is probably the result of specific P1b binding and consequent stabilization, additional experiments are necessary to rule out possible effects of P1b in enhancing 21-nt small RNA synthesis or 24-nt small RNA degradation, or in repression of the accumulation of the 24-nt species.…”
Section: Discussionmentioning
confidence: 57%
“…1). Picea abies (Norway spruce) lacks 24 nucleotide sRNAs, and it has previously been reported that Pinus contorta also lacks 24 nucleotide siRNAs 19 , which suggests that this is a conserved feature of the Pinaceae family. However, the presence of a strong 24 nucleotide size class in Cycas rumphii, and a small, but still present 24 nucleotide size class in both Ginkgo biloba and in the fern Marsilea quadrifolia suggests that the 24 nucleotide class of sRNAs originated before gymnosperm diversification.…”
Section: Resultsmentioning
confidence: 99%
“…sRNA-seq samples from several non-angiosperm plants lack an immediately obvious signature of abundant 24-nt RNAs, including mosses (Axtell and Bartel, 2005;Arazi et al, 2005), lycophytes You et al, 2017), conifers (Dolgosheina et al, 2008;Montes et al, 2014). These observations led to the suggestion that, unlike phasiRNAs and miRNAs, hc-siRNAs were not universal features found in all land plants (Dolgosheina et al, 2008).…”
Section: Conservation Evolution and Annotations Of Endogenouse Sirnasmentioning
confidence: 99%
“…These observations led to the suggestion that, unlike phasiRNAs and miRNAs, hc-siRNAs were not universal features found in all land plants (Dolgosheina et al, 2008). However, homologs of key genes known to be responsible for hcsiRNA biogenesis and function in angiosperms clearly exist in diverse plant lineages (Zong et al, 2009;Banks et al, 2011;Huang et al, 2015;Wang and Ma, 2015;You et al, 2017).…”
Section: Conservation Evolution and Annotations Of Endogenouse Sirnasmentioning
confidence: 99%